Research of the course design based on project-based learning for college computer major - Song, Guanghui; Wang, Chengbo; Nie, Yan; Chen, Genlang (2020 International Conference on Big Data and Informatization Education (ICBDIE), 2020)
This study describes the course design method based on project-based learning (PBL) for college computer major, which includes two parts: a step-by-step decomposition course design method and a hybrid teaching model combining online and offline. These two teaching reform methods take PBL as the core, integrate the engineering training content of computer specialized courses, and finally form a unified major project. The results of the surveys and the final grade show that the teaching reform methods encourage students' motivation and improve their ability. The students not only acquire better technical training, but also improve their specialized skills. This paper is also pointed out that the course design based on PBL requires to be further promoted and implemented.